(untitled) (Comprehensive Journal of Science, 2025)
Helicobacter pylori is one of the most common bacterial infections worldwide. This bacterium causes chronic inflammation of the stomach lining, leading to numerous diseases such as ulcers and chronic gastritis. Anemia is one of the most prevalent health problems globally and directly impacts physical activity and the body’s immune system.This study aimed to determine the prevalence of H. pylori and its relationship to anemia in the city of Zliten during 2024. The importance of the study lies in the potential relationship between H. pylori infection and the occurrence of anemia, as the bacterium may affect iron absorption or consumption.The study sample included 150 cases, distributed equally between males and females, with 75 cases each, during the study period.The results of the study showed that the prevalence of H. pylori in the study sample was 48%, while the percentage of anemic patients was 74%. There was no statistically significant relationship between H. pylori infection and anemia (P-value = 0.311).The study recommends promoting early screening for H. pylori, launching awareness campaigns, and improving the health and nutritional conditions of the population.